An Aza‐12‐crown‐4 Ether‐Substituted Naphthalene Diimide Chemosensor for the Detection of Lithium Ion. Issue 35 (12th December 2017) - Hangarge, Rahul V.; La, Duong Duc; Boguslavsky, Miron; Jones, Lathe A.; Kim, Yong Shin; Bhosale, Sheshanath V.
Abstract: We synthesised aza‐12‐crown‐4 ether‐substituted naphthalene diimide (NDI‐12‐C‐4) and demonstrated its properties as an fluorescent and colorimetric sensor. The NDI‐12‐C‐4 uses the aza‐12‐crown‐4 moiety to bind Li + ion selectively over larger monovalent cation such as Cs +, Na + and K + . The sensor is chemically stable due to the crown‐ether, and the appended NDI fluorophore allows leads to optical changes exclusively for the monovalent Li + ion. UV–vis absorption, fluorescence, cyclic voltammetry (CV), 1H NMR and naked eye‐detection clearly demonstrate selective, sensitive binding of Li + ion with a detection limit of 5.0 μM. Importantly, reversible binding of Li + by NDI‐12‐C‐4 was also observed upon addition of EDTA, after which the sensor could be recovered via simple centrifugation, indicating suitability for use in a biological sensor device. Abstract : The NDI‐12‐C‐4 uses the aza‐12‐crown‐4 moiety to bind Li + ion selectively over larger monovalent cation such as Cs +, Na + and K + . The sensor is chemically stable due to the crown‐ether, and the appended NDI fluorophore allows leads to optical changes exclusively. UV–vis, fluorescence, CV, 1 H NMR and naked eye‐detection clearly demonstrate selective, sensitive binding of Li + ion with a detection limit of 5.0 μM.